Integrated assessment of land-to-river Cd fluxes and riverine Cd loads using SWAT-HM to guide management strategies. (15th May 2023) - Zhou, Lingfeng; Teng, Miaomiao; Song, Fanhao; Zhao, Xiaoli; Wu, Fengchang; Meng, Yaobin; Huang, Yuanyi; Abbaspour, Karim C.
Abstract: In 2011, China invested US9.8 billion to combat the severe heavy metal pollution in the Xiang River basin (XRB), aiming to reduce 50% of the 2008 industrial metal emissions by 2015. However, river pollution mitigation requires a holistic accounting of both point and diffuse sources, yet the detailed land-to-river metal fluxes in the XRB remain unclear. Here, by combining emissions inventories with the SWAT-HM model, we quantified the land-to-river cadmium (Cd) fluxes and riverine Cd loads across the XRB from 2000 to 2015. The model was validated against long-term historical observations of monthly streamflow and sediment load and Cd concentrations at 42, 11, and 10 gauges, respectively. The analysis of the simulation results showed that the soil erosion flux dominated the Cd exports (23.56–80.14 Mg yr −1 ). The industrial point flux decreased by 85.5% from 20.84 Mg in 2000 to 3.02 Mg in 2015. Of all the Cd inputs, approximately 54.9% (37.40 Mg yr −1 ) was finally drained into Dongting Lake; the remaining 45.1% (30.79 Mg yr −1 ) was deposited within the XRB, increasing the Cd concentration in riverbed sediment. Furthermore, in XRB's 5-order river network, the Cd concentrations in small streams (1st order and 2nd order) showed larger variability due to their low dilution capacity and intense Cd inputs. Our findings highlight the need for multi-path transport modeling to guide future management strategies and better monitoring schemes to restore the small polluted streams. Highlights: Cd fluxes in Xiang river basin from 2000 to 2015 were quantified at high resolution. Regulatory tightening resulted in a substantial decrease in industrial point flux. Soil erosion was identified as the largest source of Cd inputs. Riverbed sediment was a net sink for approximately 45.1% of Cd inputs. The dissolved Cd in small streams varied largely due to low capacity and high inputs.